2010
DOI: 10.1074/jbc.m110.160325
|View full text |Cite
|
Sign up to set email alerts
|

Plk3 Functions as an Essential Component of the Hypoxia Regulatory Pathway by Direct Phosphorylation of HIF-1α

Abstract: Polo-like kinase 3 (Plk3) plays an important role in the regulation of cell cycle progression and stress responses. Plk3 also has a tumor-suppressing activity as aging PLK3-null mice develop tumors in multiple organs. The growth of highly vascularized tumors in PLK3-null mice suggests a role for Plk3 in angiogenesis and cellular responses to hypoxia. By studying primary isogenic murine embryonic fibroblasts, we tested the hypothesis that Plk3 functions as a component in the hypoxia signaling pathway. PLK3 ؊/؊ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 25 publications
6
93
0
1
Order By: Relevance
“…S8H and S8I), indicating that the regulation of HIF-1a degradation induced by YY1 silencing occurs mainly not through the hydroxylation of proline 564. Indeed, recent reports showed that besides hydroxylation, regulation of HIF-1a protein is also mediated by multiple modification pathways (5), such as phosphorylation, SUMOylation, and degradation in cytosol (28)(29)(30)(31). Whether YY1 silencing mediated HIF-1a regulation occurs through one of these pathways, or through other pathways, which has not been reported, requires further detailed investigations.…”
Section: Discussionmentioning
confidence: 97%
“…S8H and S8I), indicating that the regulation of HIF-1a degradation induced by YY1 silencing occurs mainly not through the hydroxylation of proline 564. Indeed, recent reports showed that besides hydroxylation, regulation of HIF-1a protein is also mediated by multiple modification pathways (5), such as phosphorylation, SUMOylation, and degradation in cytosol (28)(29)(30)(31). Whether YY1 silencing mediated HIF-1a regulation occurs through one of these pathways, or through other pathways, which has not been reported, requires further detailed investigations.…”
Section: Discussionmentioning
confidence: 97%
“…The Ser657 site was previously identified as a target of PLK3, and mutation of this residue to an Ala enhances the stability of HIF-1α. 19 Therefore, we focused on the other candidate site, Ser668. Sequence alignment revealed that the Ser668 residue is highly conserved in lower species, indicating that it may be of functional importance to HIF-1α (Fig.…”
Section: Cdk1 Directly Phosphorylates Hif-1α At Serine 668 In Vitromentioning
confidence: 99%
“…16 It has also been reported that phosphorylation by glycogen synthase kinase 3 (GSK3) and Polo-like kinase 3 (PLK3) promote HIF-1α degradation, while binding to the cellular chaperone, HSP90, stabilizes HIF-1α. [17][18][19] Thus, HIF-1α expression and the transcriptional activation of HIF-1 are controlled by both oxygen-dependent and oxygen-independent mechanisms in response to extracellular stimuli and the conditions of the cellular microenvironment. The identification of novel mechanisms that regulate HIF-1α expression is extremely valuable in the effort to understand tumor progression as well as to target HIF-1 as an anti-cancer therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…HIF-2, which is composed of HIF-2α and HIF-1β subunits, is regulated by oxygen in a similar manner, although HIF-2 has a more limited tissue distribution and in some cases regulates distinct target genes (15). Mechanisms by which HIF-1α is regulated in an O 2 -independent manner have also been identified (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In addition to proteasome-dependent pathways for HIF-1α degradation, we identified a pathway by which HIF-1α can be targeted for lysosomal degradation through chaperonemediated autophagy (27), which subsequently was confirmed by others (28)(29)(30).…”
mentioning
confidence: 99%